Aggressiveness in Judokas and Team Athletes: Predictive Value of Personality Traits, Emotional Intelligence and Self-Efficacy - Stanković, Nemanja; Todorović, Dušan; Milošević, Nikola; Mitrović, Milica; Stojiljković, Nenad (Frontiers in Psychology, 2022)
Combat sports and martial arts are often associated with aggressiveness among the general public, although data on judo and/or martial arts and aggressiveness seem to be unclear. This research aims to compare athletes who have trained judo for a prolonged time (minimum 5 years) and athletes from various team sports, primarily regarding the manifestation of aggression, but also regarding personality traits, emotional intelligence, and self-efficacy. Also, the potential predictive value of personality traits, emotional intelligence, and self-efficacy for aggression within subsamples of judokas and team athletes was tested. The research findings showed that professional judo athletes are characterized by a low degree of aggression, especially low indirect and physical manifestations of aggression. In addition, the personality traits Honesty-Humility and Openness to experience are well expressed, contrary to Emotionality and Extraversion, which are less pronounced. They are also characterized by moderate general self-efficacy. On the other hand, members of team sports produced the opposite results, as they are characterized by increased aggression, pronounced traits of Emotionality and Extraversion, somewhat less pronounced traits of Honesty-Humility, Openness to new experience, and less pronounced general self-efficacy. The percentage of explained variability of aggression is slightly higher in the subsample of team sports and constitutes 49.9% of the variability, while in the subsample of judokas it constitutes 47.8% of the variability of the criteria. Practical implications, limitations, and future research directions were discussed.